Environmental improvement model for cleaner copper production and its influence on business management with structural equations - Avalos Ortecho, Edilberto Miguel (2018)
Numerous studies have assessed the benefits of cleaner production on business performance but have not yet reached conclusive results. This investigation is an attempt to make two contributions to business management. Firstly, various types of cleaner production activities are compared, as well as hard and soft kills. Secondly, this study complements existing literature that focuses on Peruvian copper mining industry. Additionally, the relationship between cleaner production and business performance was evaluated using Structural Equation Modelling (SEM). An overall positive impact of cleaner production on business performance was found. On the other hand, it was also found that high-cost cleaner production activities have a bigger contribution to financial performance compared to non-financial performance, whereas low-cost cleaner production activities have a greater contribution to non-financial performance compared with financial performance.